2013
DOI: 10.1017/s0007114513003024
|View full text |Cite
|
Sign up to set email alerts
|

Screening the ability of natural feed ingredients to interfere with the adherence of enterotoxigenicEscherichia coli(ETEC) K88 to the porcine intestinal mucus

Abstract: The inhibition of the attachment of bacteria to the intestine by receptor analogues could be a novel approach to prevent enterotoxigenic Escherichia coli (ETEC) K88-induced diarrhoea in piglets. The objective of the present study was to screen the ability of different feed ingredients (FI) to bind to ETEC K88 (adhesion test, AT) and to block its attachment to the porcine intestinal mucus (blocking test, BT) using in vitro microtitration-based models. In the AT, wheat bran (WB), casein glycomacropeptide (CGMP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 64 publications
(81 reference statements)
0
37
0
Order By: Relevance
“…Some dietary carbohydrates prevent pathogen adhesion, possibly by acting as receptor analogs that saturate the glycan-binding domains of bacterial lectins and thus prevent binding to host glycoproteins. For example, polysaccharides extracted from green olive fermentation brines prevented adhesion of ETEC K88 to IPEC-J2 cells (18) but not to intestinal mucus (35). Glycans evaluated in vivo by using the SISP model were often classified only as ethanol-soluble and ethanol-insoluble fractions derived from hydrolysis of soybean and canola meal (31) or crops (27).…”
Section: Discussionmentioning
confidence: 99%
“…Some dietary carbohydrates prevent pathogen adhesion, possibly by acting as receptor analogs that saturate the glycan-binding domains of bacterial lectins and thus prevent binding to host glycoproteins. For example, polysaccharides extracted from green olive fermentation brines prevented adhesion of ETEC K88 to IPEC-J2 cells (18) but not to intestinal mucus (35). Glycans evaluated in vivo by using the SISP model were often classified only as ethanol-soluble and ethanol-insoluble fractions derived from hydrolysis of soybean and canola meal (31) or crops (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhou et al have demonstrated that deletion of fliC (encoding the major flagellin protein) and/or the faeG (encoding the F4 major fimbrial subunit) from ETEC strain C83902 significantly reduced its ability to adhere to porcine epithelia IPEC-J2 cells, but also impacting biofilm formation and quorum sensing (32). Interestingly, another study found an alternative way to block the adherence of ETEC K88 to IPEC-J2 by using ETEC anti-adhesives, including casein glycomacropeptide, exopolysaccharide, and vegetable extract (locust bean or wheat bran) (33). Finally, studies with human milk and commercial infant formulas found that the main gangliosides (GM3, GD3, GM1) and free sialic acid (Neu5Ac) are able to impede the adhesion of several pathogenic bacteria, including ETEC (26).…”
Section: Enterotoxigenic E Coli (Etec)mentioning
confidence: 99%
“…High efforts are carried out in the search of alternatives to substitute or decrease the use of antibiotics in animal production (Allen et al 2013;Seal et al 2013). In pig production, a diverse range of feed additives has been tested like probiotics, zinc, organic acids, plant extracts, microbial by-products or dairy products and others (Roselli et al 2005;González-Ortiz et al 2014;Pluske 2013;Spitzer et al 2014). …”
Section: Introductionmentioning
confidence: 99%